A Review of Our Experience in Trans Obturator Tension Free Vaginal Tape Surgery in 16 Patients - Bakay, Kadir; Güven, Davut (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: We aim to share our surgical experience in 16 patients that were complaining of genuine stress urinary incontinence, in which trans obturator tension (TOT) free vaginal tape procedure was performed. STUDY DESIGN: 16 patients complaining of genuine stress incontinence were admitted into the study group. Patients were all multiparous with a mean age of 36 ± 3. All patients were carefully examined and urodynamically tested for diagnosis. After getting positive results as genuine stress incontinence, surgery was planned. Patients were operated using outside-inside TOT technique. RESULTS: All patients except for one were found to be completely cured of stress incontinence in the reevaluation period. Urogynecological examinations and urodynamical tests were performed to objectively confirm these foundings. Therefore our objective cure ratio in 16 patients is found to be 93.75% as well as our subjective cure ratio. CONCLUSION: TOT is described as a minimally invasive procedure that can be performed even under local anesthesia to an outpatient which is an effective and easy to learn surgical technique.